The Relationship between non-halal animals and pandemic diseases according to the Shafie School of Islamic Law - Mohamed Faiz Asyraf Razali (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper explores the connection between the consumption of certain animals and the emergence of pandemic diseases, particularly in the context of Islamic law, specifically the Shafie School. Humans have long been uncertain about which animals are suitable for daily consumption. Numerous studies have demonstrated a link between animal sources and the onset of various diseases. In recent years, several animal-origin diseases have become pandemics, such as SARS, MERS, COVID-19, and Ebola. These diseases are predominantly zoonotic, originating from animals. This research aims to investigate the relationship between pandemic diseases and animal consumption through the lens of Islamic law. The study adopts a qualitative methodology, relying on secondary data about the emergence of diseases related to animal consumption and literature on Halal principles. The findings indicate that many animals associated with disease spread are considered haram (prohibited) for consumption in Islam, including pigs, bats, and pangolins. Islamic dietary laws, or Halal principles, govern food choices based on the belief that everything consumed should be permissible according to the Quran and Hadith, as well as clean, permissible, and safe. Consequently, Islam has established specific conditions for animal consumption. The research also confirms the link between pandemic diseases and the consumption of prohibited animals, as defined by Halal principles. Halal principles offer a comprehensive framework that aligns Islamic dietary laws with contemporary human needs. The study recommends further research into the impact of Halal dietary principles on human food consumption and disease prevention.